Two-level simulation approach to evaluate the performance of autonomous wheelchairs in a hospital. (October 2020) - Castilla-Rodríguez, Iván; Arnay, Rafael; Rodríguez, Raquel; Rodríguez, Jonel
In this paper, we present the combined usage of two different simulation levels to evaluate the economic and quality-of-service impact of deploying a fleet of autonomous wheelchairs in a hospital. The first simulation level deals with the physical world and takes into account the characteristics of a real robot, such as dimensions, sensor configuration, and speed. We simulate different trajectories in order to obtain realistic transportation times that are subsequently used in the high-level simulation. This high-level simulation considers those hospital resources that are affected by the inclusion of automated wheelchairs, and computes the economic implications of partially or totally substituting the current fleet of manual wheelchairs. Our results show that switching to automated wheelchairs may be beneficial in terms not only of reduced waiting times for patients, but also of economic savings.